Comparative genomics of 40 Weissella paramesenteroides strains - Wan, Xing; Takala, Timo M.; Huynh, Vy A.; Ahonen, Susanna L.; Paulin, Lars; Björkroth, Johanna; Sironen, Tarja; Kant, Ravi; Saris, Per (Frontiers in Microbiology, 2023)
Weissella strains are often detected in spontaneously fermented foods. Because of their abilities to produce lactic acid and functional exopolysaccharides as well as their probiotic traits, Weissella spp. improve not only the sensorial properties but also nutritional values of the fermented food products. However, some Weissella species have been associated with human and animal diseases. In the era of vast genomic sequencing, new genomic/genome data are becoming available to the public on daily pace. Detailed genomic analyses are due to provide a full understanding of individual Weissella species. In this study, the genomes of six Weissella paramesenteroides strains were de novo sequenced. The genomes of 42 W. paramesenteroides strains were compared to discover their metabolic and functional potentials in food fermentation. Comparative genomics and metabolic pathway reconstructions revealed that W. paramesenteroides is a compact group of heterofermentative bacteria with good capacity of producing secondary metabolites and vitamin Bs. Since the strains rarely harboured plasmid DNA, they did not commonly possess the genes associated with bacteriocin production. All 42 strains were shown to bear vanT gene from the glycopeptide resistance gene cluster vanG. Yet none of the strains carried virulence genes.